A group version of the OurRelationship program within residential substance use treatment: preliminary evidence for improving responses to romantic relationship conflict for those dealing with substance misuse - Karantzas, Gery C.; Staiger, Petra K.; Romano, Daniel A.; Curtis, Ashlee; Bruscella, Courtney; Miller, Peter G.; Gruenert, Stefan; Toumbourou, John W.; Doss, Brian D.; Christensen, Andrew (Frontiers in Psychology, 2024)
The aim of this study was to pilot an adapted version of an online relationships program with residents in treatment for alcohol and other drugs (AOD). The OurRelationship (OR) Program, which is based on Integrative Behavioral Couples Therapy, was piloted in a group-based format to determine whether residents' participation in the program would result in decreases in residents' destructive responses and increases in constructive responses to relationship conflict scenarios as well as reductions in negative affect experienced during these conflict scenarios.Residents (N=104) across six residential facilities participated in the pilot over four weeks. Pre and post program completion, residents read three vignettes in which they were asked to imagine themselves as experiencing each of the three relationship conflicts with a romantic partner. After reading each vignette, residents completed assessments related to their constructive and destructive behavioral responses to each vignette as well as the degree to which they experienced negative affect. Pre-post comparisons across the three vignettes revealed residents reported reductions in destructive behavioral responses and anger (ds -.31 to -.58) as well as increases in constructive responses (ds .33 to .77). The findings provide proof-of-concept regarding the application of programs to address the relationship difficulties experienced by those in AOD treatment. Future research into control trials of the OR program within the AOD sector can help to establish the effectiveness of relationship programs in helping to address the relationship problems of this vulnerable population.